Bioactive Compounds from Brown Algae - Ulber, Roland (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Brown algae comprise approx. 2040 species grown in various climatic conditions. They represent a reservoir of various bioactive compounds, including fucoidan, alginate, phlorotannins, and fucoxanthins. They have shown an array of applications in pharmaceutical and medical fields. Hence, the Guest Editor invites all interested authors to submit their contributions to the current issue in Marine Drugs entitled "Bioactive Compounds from Brown Algae". It aims to highlight different aspects of bioactive compounds found in brown algae, in either research or review articles. Specifically, we are interested in downstream processes, chemistry, biotechnology, and applications of, for example, heteropolysaccharides and other brown algae bioactives. In addition, the structure elucidation and enzymatic modification of these components are also within the scope of the present Issue.